1979
DOI: 10.1111/j.1399-6576.1979.tb01446.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Lung Function Following Hip Arthroplasty and Preoperative Normovolemic Hemodilution

Abstract: The effect of preoperative normovolemic hemodilution with dextran 70 as dilutional agent on postoperative regional lung function was evaluated in patients undergoing hip arthroplasty in the lateral decubitus position. The major part of the surgical blood loss of these patients was replaced with the received autologous blood. The results obtained were compared to changes in a group of patients in whom the operative bleeding was replaced with bank blood. Regional lung function, as studied with Xe133 radiospirome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The allogeneic transfusion rates were 2 (12.5%), 1 (6.25%), 8 (50%), and 10 (67%), respectively, indicating that ANH was as effective as PAD, and that both were superior to autologous blood salvage alone [20]. Some additional clinical studies in other surgical settings are summarized in table 6 [25, 26, 27, 28, 29, 30]. However, none of these reports studied the effect of ANH in total knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…The allogeneic transfusion rates were 2 (12.5%), 1 (6.25%), 8 (50%), and 10 (67%), respectively, indicating that ANH was as effective as PAD, and that both were superior to autologous blood salvage alone [20]. Some additional clinical studies in other surgical settings are summarized in table 6 [25, 26, 27, 28, 29, 30]. However, none of these reports studied the effect of ANH in total knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Correspondence to: Dr S R Bennett FFARCS, Thoraxkliniken, Norrlands University Hospital, Umea 901-85, Sweden for many years have suggested that haemodilution is not only safe in selected patients, including the elderly (10)(11)(12)(13)(14), but have gone on to demonstrate an 'optimum haematocrit' in the surgical patient (15). The lack of adverse cardiovascular and respiratory side-effects during haemodilution has been well documented (16,17).…”
Section: His Colleagues Whomentioning
confidence: 99%
“…If necessary, the hematocrit should be adjusted at the end of surgery to a level of about 30%, i.e., the values for patients undergoing preoperative hemodilution. In addition to the studies reviewed previously [10], more recent reports in the literature on pre-and intraoperative hemodilution confirm that hematocrit values of 27-30% are safely tolerated by patients undergoing general surgery [39], thoracic surgery [40], vascular, coronary, and open-heart surgery [29,[41][42][43][44][45][46], liver and tremor resection in children [47,48], orthopedic surgery and total hip replacement [39,[49][50][51][52], orthopedic surgery in children [52,53], and neurosurgery [54].…”
Section: Why Do Surgical Patients Tolerate Hematocrit Levels Lower Th...mentioning
confidence: 94%